012 Encephalitis. Issue 10 (24th September 2010) - Turtle, L
Abstract : Abstract: Encephalitis is a rare but important neurological emergency. Encephalitis means diffuse inflammation of brain matter, but there is no universal clinical definition. A recently proposed clinical definition is encephalopathy lasting for at least 24 hours plus 2 of: fever, WBC in the CSF, characteristic changes on CT, MRI or EEG and focal neurological signs. Strictly speaking it should be a tissue diagnosis, though it very rarely is. Encephalitis affects around 1.5/100 000 population/year in the UK, though some studies show an incidence of up to 7–8 cases/100 000/year. Encephalitis is more common at the extremes of age. Although patients with proven encephalitis are rare, patients with suspected encephalitis are not. An audit in NW England found that 20 patients started treatment for encephalitis for only 1 who had the diagnosis proven. Many such patients are not well managed, particularly with respect to poor investigation, delay in LP and unnecessary neuroimaging before LP is carried out. There are multiple causes of encephalitis, however most studies show around 60% of cases are unexplained. Viral encephalitis is the commonest diagnosis made, usually with HSV as the leading agent. VZV and enteroviruses are also commonly found, though enteroviruses are more frequently associated with meningitis. In Asia Japanese encephalitis virus is a very important cause of encephalitis, and is probably the most significant cause of epidemic encephalitis in the world. There are many other causes; other viruses, bacteria such as Listeria and M. tuberculosis and parasites ( Toxoplasma ). In immunocompromised patients the differential is even wider, for example CMV. Another large group is immune mediated encephalitis. Several arthropod borne viruses (arboviruses) cause encephalitis so outbreaks of encephalitis may be the presenting phenomenon of new and emerging infections. The most notorious recent example was the rapid spread of West Nile virus across the USA following the outbreak in New York in 1999. In the UK encephalitis is a notifiable disease but perhaps as many as 90% of cases are not reported. Unfortunately the outcome from encephalitis is poor with many patients suffering permanent neurological sequelae. There is now an increasing effort in the UK to improve the management of encephalitis. A large prospective study, funded by the NIHR, will soon be starting. This will include natural history studies on outcome and a pilot study of a new national guideline. The UK boasts an excellent patient support and information group; the Encephalitis society.